2021
DOI: 10.1180/mgm.2021.29
|View full text |Cite
|
Sign up to set email alerts
|

In situtrace elements and S isotope systematics for growth zoning in sphalerite from MVT deposits: A case study of Nayongzhi, South China

Abstract: Zoning texture in sphalerite has been described in many studies, although its genesis and ore formation process are poorly constrained. In this investigation, we compare the in situ trace element and isotopic composition of colour-zoned sphalerites from Nayongzhi, South China, to explain the zoning growth process. Petrographic observations identified two broad types of zoned sphalerite, core–rim (CR) and core–mantle–rim (CMR) textures. Each zoned sphalerite displays two or three colour zones, including brown c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Up to now, the technology is still in the stage of popularization. As China's development ability in machine vision hardware and software is not very strong, there is a certain gap between domestic MVT and foreign MVT, resulting in high development cost and low efficiency of related products [12]. In recent years, domestic research institutes, universities, and related enterprises have increased their research on MVT and applied the technology to industrial sites, such as electronic manufacturing, semiconductor industry, and pharmaceutical industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Up to now, the technology is still in the stage of popularization. As China's development ability in machine vision hardware and software is not very strong, there is a certain gap between domestic MVT and foreign MVT, resulting in high development cost and low efficiency of related products [12]. In recent years, domestic research institutes, universities, and related enterprises have increased their research on MVT and applied the technology to industrial sites, such as electronic manufacturing, semiconductor industry, and pharmaceutical industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have reported bulk S isotopic compositions of sphalerite from the Nayongzhi deposit, which have δ 34 S = 17.2–25.5‰ (Jin et al., 2016; Zhou et al., 2018), whereas the in situ S isotopic compositions of different colored sphalerite zones vary from 22.3 to 27.9‰ (Wei et al., 2021). In contrast, Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Geological map of the Wuzhishan anticline showing the location of Zn-Pb ore deposits. The figure was taken and modified fromWei et al (2018Wei et al ( , 2021.…”
mentioning
confidence: 99%
“…Blocks of two standards (one NIST 610 and one GSE-2G) and one MASS-1 sulfide standard analyses were followed by five to eight unknown samples. For sphalerite, the following 18 isotopes were measured (with their respective dwell times in milliseconds listed in parentheses): 34 S, 55 Mn, 57 Fe, 59 Co, 60 Ni, 65 Cu, 66 Zn, 71 Ga, 74 Ge, 75 As, 77 Se, 107 Ag, 111 Cd, 118 Sn, 121 Sb, 126 Hg, 205 Tl, and 208 Pb, corresponding to a total dwell time of 180 ms. The MASS-1 sulfide standard [37] was used as the primary standard for calibrating 34 S, 55 Mn, 57 Fe, 59 Co, 60 Ni, 65 Cu, 66 Zn, 71 Ga, 74 Ge, 75 As, 77 Se, 107 Ag, 111 Cd, 118 Sn, 121 Sb, 126 Hg, 205 Tl, and 208 Pb.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…In these ternary plots, the Nanmushu sphalerite also falls into the MVT field, which is clearly different from the SEDEX, VMS, and Skarn deposits. [5,13,14,[65][66][67][68][69][70][71]; MVT data are collected from references [3,5,18,30,[41][42][43]50,66,[72][73][74]; SEDEX data are collected from references [75][76][77][78][79]; Skarn data are collected from references [3,5,13,14,67,[80][81][82]; and VMS data are collected from references [3,5,66,83,84].…”
Section: Genesis Of Ore Depositmentioning
confidence: 99%